# Simplify the following: 2√3/3 - √3/6

**Solution:**

Given, 2√3/3 - √3/6

We have to simplify the expression.

Taking out common terms,

2√3/3 - √3/6 = √3(2/3 - 1/6)

= √3((4-1)/6)

= √3(3/6)

= √3(1/2)

= √3/2

Therefore, 2√3/3 - √3/6 = √3/2

**✦ Try This: **Simplify the following: 4√2/3 - √2/6

**☛ Also Check: **NCERT Solutions for Class 9 Maths Chapter 1

**NCERT Exemplar Class 9 Maths Exercise 1.3 Problem 9(ix)**

## Simplify the following: 2√3/3 - √3/6

**Summary:**

Irrational numbers cannot be expressed in the form of a ratio, such as p/q, where p and q are integers, q≠0. The simplified form of 2√3/3 - √3/6 is √3/2

**☛ Related Questions:**

Math worksheets and

visual curriculum

visual curriculum